Insights into lignocellulosic fiber feedstock and its impact on pulp and paper manufacturing: A comprehensive review - Hawanis, Husain Siti Nor; Ahmad Ilyas, Rushdan; Jalil, Rafidah; Ibrahim, Rushdan; A. Majid, Rohah; Ab Hamid, Nur Hafizah (Elsevier, 2024)
Concerns about the depletion of wood resources and the environmental impact of increasing demand for paper goods have led to the quest for alternate sources of fiber for pulp and paper manufacture. Non-wood fibers, such as agricultural residues, are seen as a sustainable and renewable source of fiber. However, due to changes in chemical composition, unpredictability, and processing methods, their utilization offers obstacles. Nonetheless, ongoing research in non-wood fiber pulping drives the development of new methods and technologies to enhance non-wood fibers' processability. Kraft pulping, known for efficacy and adaptability. This review provides comprehensive insights into the utilization of lignocellulosic non-wood fibers as sustainable alternatives to wood in pulp and paper manufacturing, backed by recent research. It explores the feasibility of non-wood fiber utilization and assesses various pulping processes' impacts on their properties. Notably, innovative pulping methodologies have emerged, addressing conventional approach shortcomings. Further research should focus on refining innovative pulping techniques and exploring alternative compounds to replace conventional chemicals, reducing ecological footprints. Efforts are needed to enhance non-wood fibers' processability through technology development. Collaboration among researchers, industry, and policymakers is vital to drive advancements and facilitate widespread non-wood fiber adoption. Exploring non-wood fiber applications beyond pulp and paper manufacturing could diversify fiber supply chains sustainably. In summary, the future of non-wood fibers in the pulp and paper industry is promising, with ongoing research and innovation expected to unlock their full potential, driving positive environmental and economic outcomes. © 2024 Elsevier B.V.